Analisis Perkiraan Biaya F&B (Makanan & Minuman) Dengan Metode Moving Average Pada Pola E-Commerce Hotel XYZ - I Gede Putu Megayasa; I Made Candiasa; Gede Rasben Dantes (Journal of Information System Research (JOSH), 2022)
Forecasting is made because of the complexity and uncertainty faced by decision makers (5 and = 0.9). The use of these two forecasting methods is to compare which forecasting method is more accurate and closer to the true value. The research method used starts from collecting data, determining forecast methods, calculating forecasts, selecting forecasts, and drawing conclusions. The calculation of the estimated results for F&B costs at Puri Santrian Hotel Sanur is based on the Single Moving Average MA. 3 of 1.143.941.601,89, the MAD value of 113.205.931, and the Single Moving Average (MA.3) of 112.700. Using exponential smoothing (ES=0.9), the forecast value for the period ending January 2017 is 898.343.836,01 with an MAD value of 115.870.591,88 and an MSE value (ES=0.9) of 21.219. Data series using the moving average method (Single Moving Average Method and Exponential Smoothing Method) can be done by calculating the minimum error values MAD and MSE, using the two methods above MAD and MSE after calculating the error, MAD is 3.686.238.23 (absolute value) and the MSE value is 13.588.352.306.255.